Rehabilitation of Patients after Anterior Cruciate Ligament Reconstruction - Karbowski, Maciej; Głowacka-Mrotek, Iwona; Nowacka, Krystyna; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
Damage to the ligaments of the knee is a very common problem. According to statistics, it is the anterior cruciate ligament that is most often injured. People practicing so-called pivoting sports (sports that involve sudden turns and direction changes) are particularly vulnerable to the rupture of the ACL. For patients who suffer from an ACL injury, the main way to full recovery is to restore the continuity of the ligamentous structures using surgery preceded by a comprehensive pre-operative rehabilitation. After undergoing the reconstructive surgery, the personalized rehabilitation should be implemented and adapted to the possibilities and progress of the patient. The main aim of this aticle was to present the methods used throughout the rehabilitation process of patients, who underwent the ACL reconstruction. An effective postoperative rehabilitation should consist of kinesiotherapy, the course of which is adapted specifically to the stage in which the patient currently is. The exercises suitable for the initial phase should not increase the acute symptoms. They should, however, start restoring motion range and rebuilding muscular strength. The demands placed on the patient should be continuously made harder throughout the rehabilitation process and should increase their independence leading to restoration of a normal walking pattern. A very important part of rehabilitation is the training that rebuilds proprioception in the knee joint. Kinesiotherapy should be varied with activities, such as swimming or riding a stationary bike. In the final stages of rehabilitation, the elements of the sport practiced by the patient should be implemented. Improvement is aided by physiotherapy, elements of a manual therapy and kinesiology taping.